Islamic environmental ethics and green technology practices for park design: potential of the adaptation in Taman Tasik Titiwangsa - Zulkifely, Zur Atiiqa; Tengku Aziz, Tengku Anisah; Abu Bakar, Aniza (2013)
Current global environmental problems such as global warming, urban heat island impact, water contamination and deforestation lead towards a great challenge to present and future generation in providing its solution. The role of design intervention in minimizing and mitigating such problems seems to be vital. Therefore, developing an environmental friendly park in an urban setting is highly needed to mitigate the environmental degradation, improve quality of life and connect man and the environment through the patches of green space. Park as the public space may provide a vital outdoor space which brings comfort to the people. Hence, the demand for good and practical park design has been increasing. As a Muslim, our life is should be based on the Islamic principles as referred to the Al-Quran and Sunnah Hence, good design guidelines should also be derived from the Islamic principles as Islam provides a comprehensive way of life. In studying the Islamic ethics, these three prior relationships are explored; man and God, man and the environment and man and man, followed by special focus on sustainability in Islam in an attempt of a holistic approach. Therefore, green technology practices in park design are important in sustaining the environment. This research is an attempt in deriving a park design guideline which is based from the Islamic principles and ethics, with further observation on the application and potential application of green technology at a case study site which is Taman Tasik Titiwangsa. The main techniques adopted are content analysis and observation. The content analysis is applied on several surah in Al-Quran and the al-hadith that mentioned on the environment, as well as the park design guideline from Jabatan Landskap Negara (JLN) and Jabatan Perancangan Bandar dan Desa (JPBD). The output from the content analysis is translated as a guide to observe design elements such as; spaces, forms and activities at the site. The results suggested that the Islamic environmental principles and ethics could be integrated and applied into the park design guideline and associated with the arrangement of spaces and the interaction of people. This paper also suggested that the green technology application is in-line with the Islamic principles and ethics on the environment and could be instilled together with the design elements such as at the gathering points and pathway, on the land as well as in the water bodies. Therefore, the design recommended for the adaptation of green technology that addresses Islamic environmental principles and ethics are suggested at one location only at the case study site because the overall site is quite large to be covered by researchers. Keywords: Islamic environmental ethics, green technology, park design guidelines